VALUE CO-DESTRUCTION: ANALISA FAKTOR PADA START-UP BUSINESS MAHASISWA [VALUE CO-DESTRUCTION: AN ANALYSIS OF FACTORS FOR BUSINESS START-UP STUDENTS] - Deandra Vidyanata; Teofilus Teofilus; Timotius F. C. W. Sutrisno; Ruth Violina Gelombang (Universitas Pelita Harapan, 2020)
This study aims to examine the factors which cause value co-destruction and how to overcome value co-destruction in a Start-up Business. This study uses a quantitative approach with a total sample of 170 business start-up projects of Ciputra University students. The data collection method used is questionnaires and the research data is tested by factor analysis. The result of this study indicates that product information, interaction, innovation, and service can influence the emergence of value co-destruction. These four factors must be considered by every business start-up student.Abstrak Bahasa Indonesia Penelitian ini bertujuan untuk menguji faktor-faktor yang menyebabkan value co-destruction dan bagaimana cara mengatasi Penghancuran value co-destruction di Bisnis yang baru dimulai. Penelitian ini menggunakan pendekatan kuantitatif dengan total sampel 170 proyek start-up bisnis mahasiswa Universitas Ciputra. Metode pengumpulan data yang digunakan adalah kuesioner dan data penelitian diuji dengan analisis faktor. Hasil penelitian ini menunjukkan bahwa informasi produk, interaktif, inovasi, dan layanan dapat mempengaruhi munculnya value co-destruction. Keempat faktor ini harus dipertimbangkan dalam setiap siswa pemula bisnis.